Chief Executive Officer (CEO) Characteristics and Corporate Social Responsibility Disclosure Among NonFinancial Listed Firms in Malaysia - Mohd Waliuddin, Mohd Razali; Nurdiana Natasha, Azizan; Yau, Josephine Tan Hwang; Janifer, Lunyai; Sharifah Sabrina, Syed Ali (UTHM, 2017)
The purpose of this research is to examine the link between Chief Executive Officer’s (CEO) characteristics and Corporate Social Responsibility (CSR) disclosure. The sample data used in this research comprises of 201 non-financial firms listed on the Bursa Malaysia for the period 2013- 2015. CEO’s characteristics that have been examined in this study are CEO’s gender, working experience, and educational background. All non-financial data were collected from annual reports and financial data were collected from Data stream. This study proves that CEOs with humanity or social sciences educational background such as law, accounting, and business are more likely to engage in CSR disclosure by taking into account stakeholders’ interests. CEOs in the field of science are also tend to engage more in CSR disclosure. Besides that, we also found that larger firms tend to have higher disclosure of their CSR activities.